Diversity of niger (Guizotia abyssinica L.F. Cass.) landraces for major agronomic traits: Diversity of niger (Guizotia abyssinica L.F. Cass.) landraces for major agronomic traits - D P MEGHANA; H D PUSHPA; M SUJATHA; HELAN BABY THOMAS; PRADUMAN YADAV; CH KRISHNA CHAITANYA; HUSSAIN BASHA; RAJANI BISEN; PRASHANT K JAGTAP (Journal of Oilseeds Research, 2023)
A diverse set of 870 Indian niger accessions were evaluated for various quantitative traits. Principle component analysis revealed the contribution of first three PCs to maximum variability and clustering analysis separated the accessions into eight different clusters. A significant diversity was revealed among these accessions and they can be further used as trait-specific donors in hybridization program for improvement of seed yield related traits in niger.